Synthesis, characterization and antioxidant activity of 1,3,4-oxadiazoles bearing an indole ring - Kong, Kian Liang (2019)
1,3,4-oxadiazoles have been widely studied by many researchers in various fields. Due to its heterocyclic structure, 1,3,4-oxadiazoles possess of many biological and pharmacological activities such as antibacterial, anticancer, antiinflammatory, antimalarial and antioxidant activities. In this project, carboxylic acid hydrazide was synthesized and act as a starting material for the synthesis of 1,3,4-oxadiazoles. A total of four 1,3,4-oxadiazoles have been synthesized. The structure of carboxylic acid hydrazide and 1,3,4-oxadiazoles were elucidated and characterized through various instrumental analysis such as melting point, FTIR, 1H NMR, 13C NMR, DEPT, HMQC and HMBC. The determination of antioxidant activity of the carboxylic acid hydrazide and 1,3,4-oxadiazoles was carried out through DPPH assay with BHT as standard reference. All the compounds synthesized exhibit weak antioxidant activity (> 200 ppm) as compared to BHT.